What do playing the trombone, becoming a comedian and teaching in executive education programs have in common? (Reflections from decades of bad jokes and wrong notes). (October 2016) - Straussman, Jeffrey D
Repertoire: –a stock of plays, dances, or pieces that a company or a performer knows or is prepared to perform. –the whole body of items that are regularly performed. –a stock of skills or types of behavior that a person habitually uses. https://www.google.com/#q=definition+of+repertoire Assessing the impact of teaching on student learning is an educational enterprise that has been going on for many years. Less common, however, is the evaluation of the impact of teaching on the instructor. That is, how does increasing teaching experience both in terms of the number of years doing it and the diversity of teaching experiences improve teaching? This is, of course, an empirical question. This paper focuses on one type of teaching experience and its overall contribution to improving instruction in public administration and policy. I draw from experience in short-term, non-degree teaching in executive programs (EEs). These programs are aimed at middle-level or senior government officials and may be as short as one day or as long as four weeks (on rare occasions longer). I show how this type of teaching can improve one's teaching repertoire much like a young professional trombonist (think of Tommy Dorsey in his early 20s) or a fledging comedian trying to make the big time developing a professional repertoire. One's repertoire is a combination of pedagogical technique and policy and management substance. Since short-term, non-degree teaching in EEs is different from degree-based, semester-length teaching, it presents specific challenges, especially for the novice EE instructor. As the repertoire improves via EE teaching, it is likely to transfer to more conventional graduate-level professional education. Case examples come from Hungary, the USA, China, Macedonia and Singapore.